If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-2(2X-11)=7
We move all terms to the left:
X-2(2X-11)-(7)=0
We multiply parentheses
X-4X+22-7=0
We add all the numbers together, and all the variables
-3X+15=0
We move all terms containing X to the left, all other terms to the right
-3X=-15
X=-15/-3
X=+5
| 122-(6x+13)=6(x+3)+x | | ∠A=5x−18∘ | | 20=21x | | 3d-4=0 | | 4d-1=0 | | 16/3x=2 | | -36x^2+192-144=0 | | -65+b=20 | | 11u=12+7u | | 11u=12 | | 11x-170=3x-10 | | -144+a=12 | | 0.05n+0.06=1.55 | | x−4=12x+713x-4=12x+7 | | (x+12)+23x=423x+12+23x=4 | | 13x-16=7-4x | | (T+140)+t=540 | | 2.25x=9.75x | | 6x+2=0.5(13x-8) | | 1/5x-1/2x=6 | | X^2-18x-19=31 | | 7x-`16=5x+8 | | x+3x+x+2x=42 | | 0.05^x=0.25 | | 6x+5=0.5(13x-3) | | 2-500000/x^2=0 | | 4b²+8b+7=4 | | 2y+y=120 | | 38=8u | | M=7/6t+17 | | -50=-3x+5(6x+17) | | 3x+13+x-8+x=180 |